PENGARUH TEKNIK PERNAPASAN BUTEYKO TERHADAP SKOR KONTROL ASMA - Pradnyawati, Yunita (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Asthma is an obstructive intermittent airway disease which reversible characterized where the trachea and bronchi are responding hyperactive to certain stimuli which it is signed by airway constriction, results in dyspnea, cough and wheezing. One of the complementary therapies that can be used in the management of asthma is the Buteyko breathing technique. Buteyko breathing technique helps balance the levels of carbon dioxide in the blood that can reduce the incidence of hypoxia, hyperventilation and apnea during sleep in patients with asthma. This study aims to determine the effect of the Buteyko breathing technique on asthma control scores in the Pulmonary Polyclinic of RSUD Wangaya. This research using quasi experimental design with nonequivalent control group. Samples were 20 asthma patients recruited using purposive sampling, divided into experimental and control group. Buteyko technique was given to experimental group once a day minimum for 20 minutes for four weeks. Asthma control scores pre-test and post-test in both groups were assessed using Asthma Control Test questionnaire. This study shows that the average value of asthma control score in experimental group is 5,00 whereas only 0,50 in control group. Based on the independent sample t-test, this difference was statistically significant, with Sig. (2-tailed) of 0,000, which means there is the effect of Buteyko breathing technique for asthma control scores in the Pulmonary Polyclinic of RSUD Wangaya. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Asthma; Buteyko Breathing Technique; Asthma Control Scores